SELF-COMPASSION DAN PARENTING STRESS PADA IBU RUMAH TANGGA - Dyah Ayu R.; Martanti Martanti; Narastri Insan Utami (PSIKOSAINS (Jurnal Penelitian dan Pemikiran Psikologi), 2024)
Background: The many demands of a mother's role in the household, especially parenting, cause mothers to experience parenting stress. Self-compassion in housewives is thought to have a relationship with parenting stress. Objective: The purpose of this study was to determine the relationship between self-compassion and parenting stress in housewives. Method: This research is a correlational quantitative research with 120 housewives as the research subjects. Sampling using purposive sampling technique. Data collection methods using two scales namely Self-Compassion Scale and Parenting Stress Scale Data analysis using Pearson product moment correlation. Results: The results of the study obtained a correlation coefficient of -0.441 with a significance level of 0.000 (p < 0.001), it can be interpreted that the research hypothesis is accepted. Conclusion: There is a significant negative relationship between self-compassion and parenting stress in housewives. So that the higher the self-compassion possessed, the lower the tendency of parenting stress experienced by housewives.